Age determination using feldspar: Evaluating fading-correction model performance. (December 2018) - King, Georgina E.; Burow, Christoph; Roberts, Helen M.; Pearce, Nicholas J.G.
Abstract: The recent introduction of post-IR IRSL measurement protocols has prompted a resurgence in luminescence applications using feldspar, some of which are affected by anomalous fading related signal loss. Many fading-corrected feldspar ages are reported in the literature, however few of those ages have been corrected using the model of Huntley (2006) [Huntley, D.J., 2006. An explanation of the power-law decay of luminescence. Journal of Physics: Condensed Matter 18(4), 1359–1365] . Here we present a new R function that calculates fading-corrected ages using the model of Huntley (2006), implemented with either a single-saturating exponential (1EXP) or general-order kinetic (GOK) fit. We evaluate the performance of the model through (i) contrasting measured and modelled field saturation values for a suite of 41 published saturated samples, and (ii) through using the model to fading-correct feldspar ages of samples with independent age control. Our results indicate that when implemented with 1EXP this model has an accuracy of 10% for predicting sample saturation, but that independent ages may be overestimated when the model is used to fading-correct samples across a range of timescales. In contrast, providing that the dose response curve has been characterised beyond 600 Gy, implementing the Huntley (2006) model with a GOK fit yields accurate age estimations. Modelled age overestimation for 1EXP is associated with dose response curve deviation from a single-saturating exponential. Finally we contrast the laboratory measured light levels of a suite of 50 saturated samples with their corresponding fading rates. We show that these saturated samples may yield D e values below 2D 0, and thus that 2D 0 is not an effective screening criterion for sample saturation where no anomalous fading correction is made. Highlights: Fading correction of feldspar luminescence is explored using known age samples. Dose response deviation from a single saturating exponential causes age overestimation. A general order kinetic fit results in accurate age determination. 2D0 cannot be used to evaluate feldspar saturation, unless fading is corrected for.